Examining memory for ritualized gesture in complex causal sequences - Kapitany, R; Kavanagh, C; Whitehouse, H; Nielsen, M (Elsevier, 2018)
Humans have created and maintained an exponentially large and sophisticated behavioral corpus over evolutionary time. In no small part this was achieved due to our tendency to imitate behaviours rather than to emulate outcomes. This tendency, however, can lead to inefficiency and redundancy in our behavioral repertoires. Drawing on evidence from multiple fields of psychology, we propose two novel competing hypotheses. The ‘catalyst hypothesis’ suggests that low (but not high) proportions of ritualized gesture in instrumental action sequences will improve subsequent recall of the entire action sequence (without itself enhancing the instrumental utility of the sequence). Conversely, the ‘cost hypothesis’ suggests that increasing proportions of ritualized gesture will impair recall, due to the introduction of cognitive load. The null hypothesis states that ritualized gestures are neither beneficial nor costly. In a pre-registered experiment, we presented participants with multiple versions of two complicated 2-min action sequences in which we varied the proportion of ritualized gesture. We then quantified the influence ritualized gesture had on recall for individuals gestures, overall outcomes, and described detail. We found clear evidence that high proportions of ritualized gestures impair recall for individual gestures and overall success, and weak evidence that low proportions increase overall success. At present, we may reject the null, but cannot rule out either of our competing hypotheses. We discuss potential implications for cultural evolution, and generate competing predictions that allow for adjudication between Ritual Modes theory (Whitehouse, 2004) and the ‘Cognitive Resource Depletion’ account of Religious Interaction (Schjoedt et al., 2013). All files (including data and syntax) are freely available at https://osf.io/spz68/.